Analisis Dampak Pandemi Covid-19 Terhadap Proses Belajar Siswa di SMAN 3 Jember - I Ketut Mahardika; Adianto Syahbana; Alya Salma Qothrun Nada; Nilna Ulfia; Yenni Eka Septiani; Rizka Elan Fadilah; Firdha Yusmar (Peneliti.net, 2022)
The Covid-19 pandemic has had a negative impact on the world of education. The impact that can be felt is that all teaching and learning activities are carried out online or online without meeting face to face, this is because all activities are limited which aims to prevent the spread of the Covid-19 virus. This study aims to find out what impact the Covid-19 pandemic has on the learning development of SMAN 3 Jember students, where later this research will produce information or an overview of the impact of online learning on the development of student learning. The method used in this study is a qualitative research method, in which the research procedure will use descriptive data in the form of written or spoken words from related parties. The data collected in this study include primary and secondary data. Data collection was carried out by direct observation and interviews with related parties, namely students, BK teachers, nad parents.